Ecological risk assessment of species impacted by fisheries in waters off eastern Taiwan. (12th March 2020) - Lin, Chih‐Yu; Wang, Sheng‐Ping; Chiang, Wei‐Chuan; Griffiths, Shane; Yeh, Hsin‐Ming
Abstract: An ecological risk assessment was undertaken using productivity‐susceptibility analysis (PSA) to determine the relative vulnerability of 52 species caught by fisheries in the waters off eastern Taiwan. Overall, eight and 20 species were classified as having high and moderate vulnerability, respectively, and the remaining 24 species were classified as having low vulnerability. The species with the highest vulnerability scores were caught mainly by longline and gillnet fisheries, highlighting the need for improved data collection to facilitate a more detailed investigation using more quantitative methods. The data quality analysis indicated that the quality of data was classified as "moderate" for economically important species. However, many species were considered data‐limited and thus collecting high‐resolution catch and effort information and conducting biological studies, especially relating to age, growth and reproduction, are recommended to improve the reliability of outputs from data‐limited assessments such as PSA.